Investigation of orbitofrontal sulcogyral pattern in chronic schizophrenia. Issue 2 (30th November 2015) - Cropley, Vanessa L.; Bartholomeusz, Cali F.; Wu, Peter; Wood, Stephen J.; Proffitt, Tina; Brewer, Warrick J.; Desmond, Patricia M.; Velakoulis, Dennis; Pantelis, Christos
Abstract: Abnormalities of orbitofrontal cortex (OFC) pattern type distribution have been associated with schizophrenia-spectrum disorders. We investigated OFC pattern type in a large sample of chronic schizophrenia patients and healthy controls. We found an increased frequency of Type II but no difference in Type I or III folding pattern in the schizophrenia group in comparison to controls. Further large studies are required to investigate the diagnostic specificity of altered OFC pattern type and to confirm the distribution of pattern type in the normal population. Highlights: We investigated OFC pattern type in chronic schizophrenia patients and healthy controls. We found an increased frequency of Type II folding pattern in schizophrenia. Further studies should examine the distribution of pattern type in the normal population.